Development of an Alginate Array Platform to Decouple the Effect of Multiparametric Perturbations on Human Pluripotent Stem Cells During Pancreatic Differentiation. Issue 2 (25th January 2018) - Richardson, Thomas C.; Mathew, Shibin; Candiello, Joseph E.; Goh, Saik K.; Kumta, Prashant N.; Banerjee, Ipsita
Abstract : Human embryonic stem cells (hESC)‐derived functional cells hold great promise for regenerative cell therapy. Currently approved strategies for clinical translation requires the isolation of the hESCs‐derived cells in materials allowing transfer of reagents but preventing integration with the host. However, hESC fate is known to be sensitive to its local microenvironment, both chemical and physical. Given the complexity of hESC response to environmental parameters, it will be important to evaluate the cell response to multiple combinatorial perturbations. Such complex perturbations are best enabled by exploiting high‐throughput screening platforms. In this study, the authors report the effect of multivariate perturbations on hESC differentiation, enabled by the development of high throughput 3D alginate array platform. Specifically, the sensitivity of hESC propagation and pancreatic differentiation to substrate properties and cell culture configuration is analyzed. Cellular response to array perturbations is analyzed by quantitative imaging, and cell sensitivity was determined through statistical modeling. The results indicate that configuration is the stronger determinant of hESC proliferation and differentiation, while substrate properties fine‐tune the expression around the average levels. This platform allowed for multiparametric perturbations, and in combination with statistical modeling, allows to identify the sensitivity of hESC proliferation and fate to multiparametric modulation. Abstract : The authors developed a high throughput 3D alginate array platform that allowed for multiple combinatorial perturbations of insoluble differentiation cues on human pluripotent stem cells (hPSCs), namely hydrogel stiffness and cell–cell contact, during pancreatic differentiation. Their results indicate that while stiffness did influence proliferation and pancreatic differentiation, the effect of cell–cell contact was more significant. In combination with statistical modeling, the tools developed in this study allowed them to identify the sensitivity of hESC proliferation and fate to multiparametric modulation.